THE ISSUE OF SOVEREIGN POWER IN HENRY V AND KING LEAR - Farshid, Sima (European Scientific Journal, ESJ, 2014)
Shakespeare was quite conscious of the working of power “apparatus” due to his presence in Queen Elizabeth’s court and being aware of power relations and constant struggles in it, and he drew on that awareness to give life to the characters portrayed in his drama, namely the two plays discussed here, Henry V and King Lear. To elaborate on his depiction of power relations in those plays, I would resort to Foucault’s theory of power, especially his ideas about “sovereign” power. He contends that sovereignty was issued from the top of a hierarchical pyramid set up by the “monarchical institution” that was founded on the possession of a great amount of land and the assumption of the divine protection. In the light of Foucauldian notion of sovereignty, I would discuss Shakespeare’s depiction of Henry V’s irrefutable power and Lear’s devastated power. Shakespeare portrays Henry V as a ruler who is conscious of the operation of power “apparatus” and consequently strengthens his monarchy, whereas he presents the old Lear as a king who is ignorant of the foundations of “monarchical institution” and as a result loses his power because of his reckless decision of dividing his territory among his daughters.